Le programme Erasmus en France, en Italie et en Angleterre : sélection des étudiants et compétences migratoires - Magali Ballatore (Les éditions de la Maison des sciences de l'Homme, 2006)
Student migrations in Europe are not new. However the Erasmus program has introduced a certain type of mobility. This is not without consequences on Higher Education systems in Europe, which have their own selective, productive and integrative practices. Participating students tend to underline the benefits of the programme and their personal satisfaction, but a closer look at the programme in the three countries where the university was born and at the Erasmus student trajectories allows raising the issue of inequalities in patterns of mobility. We may ask whether latent inequalities have increased in systems which are "mass" rather than "democratic". Looking at the skills and the migratory capital already acquired by students and at the selection practices in the departments or faculties, it is obvious that this program tends to consecrate young people whose educational trajectories are, if not brilliant, at least fast and/or atypical. Moreover, the European commission's data show that reciprocity of exchanges is rarely achieved. Hence, this program seems to reinforce the pre-existing supremacy (of languages and of some institutions in particular) and the growing diversification of students' trajectories.